Edukasi Pemeliharaan Lingkungan Sehat dan Adaptasi Teknologi Melalui Kegiatan KKN - Putra, Tri Dharma; Vanessa, Vera; Gunawan, Osisca; Sadewo, Ronggo; Hafiz, Wildan Zikril; Putra, Iqbal Mahandika; Prana, lham Bagus (Journal Of Computer Science Contributions (JUCOSCO), 2024)
Technological developments have a significant impact on children's life. While the use of gadgets provides benefits and learning opportunities, it can also potentially have a negative impact on their health and development. Awareness of the dangers of gadgets and the importance of maintaining a healthy and technology- aware environment is crucial. This community service program aims to socialize the dangers of gadgets to children with a focus on raising awareness about the importance of maintaining a healthy and technology-aware environment. This program provides knowledge, understanding, and skills to children and parents so that they can use gadgets responsibly and in a balanced manner. The program is implemented through KKN activities with student participation as facilitators. The implementation methods include material delivery, group discussions, demonstrations, and other interactive activities. This activity will be carried out door-to-door in the surrounding area. This program combines knowledge about the dangers of gadgets with the need for children to maintain health and develop positive technology awareness. It is hoped that this program can increase community awareness of the dangers of gadgets on children and the importance of maintaining a healthy and technology- aware environment. Implications for further programs involve continued efforts in outreach and education to children, parents, and teachers. This program can serve as a model for similar activities in other areas with similar contexts.